Combining the Fibrinogen/Albumin Ratio and Systemic Inflammation Response Index Predicts Survival in Resectable Gastric Cancer. (25th February 2020) - Zhang, Junbin; Ding, Yongfeng; Wang, Weibin; Lu, Yimin; Wang, Haiyong; Wang, Haohao; Teng, Lisong
Abstract : Aims . Predicting the prognosis of gastric cancer using tumour-node-metastasis (TNM) staging is difficult as patients with the same TNM stage exhibit different prognoses. Methods . This study investigated the prognostic value of the preoperative fibrinogen/albumin ratio (FAR)-systemic inflammation response index (SIRI) score in resectable gastric cancer (rGC). Results . Clinicopathological features of 231 rGC patients were analysed retrospectively. Patients were divided into three groups: FAR-SIRI score 2 (FAR ≥ 0.071 and SIRI ≥ 0.84 ), 1 (FAR < 0.071 and SIRI ≥ 0.84 ), and 0 (SIRI < 0.84 ). Higher FAR-SIRI scores were associated with larger tumours, poorer differentiation, and advanced TNM stage (P < 0.05 ). Compared to those with FAR-SIRI scores of 0, patients with scores of 2 had poorer overall survival (OS). The FAR-SIRI score was an independent prognostic factor for OS in rGC. Conclusion . The present data demonstrated that FAR-SIRI scores predicted radical gastric cancer surgical outcomes and may serve as a blood marker for identifying high-risk patients.